Dungal and Donatus of Fiesole: Some Considerations on the “Scotti peregrini” and St. Brigid’s Cult in Italy - Mantegazza, Fabio (The Journal of Medieval Latin, 2025)
Abstract Among the Irishmen active in Italy during the Carolingian era, the most famous are undoubtedly Dungal of St. Denis, Pavia, and Bobbio, and Donatus of Fiesole. Both represent the typical features and interests of the “Scotti peregrini” of the time, but the information we have about them is not very certain. The former is a very elusive figure, and until a few decades ago scholars believed that several namesakes were hidden under his name. Donatus is fairly well known as a historical figure, but his literary production and the texts that gravitate around his Vita metrica sanctae Brigidae have not yet been studied in detail. In the present article, I deal with the poem O uenerande pie, a text that would seem to unite the two characters, developing an idea formulated by Mario Esposito. After a philological and historical analysis, I attempt to identify the author and receiver of the poem. I then endeavour to place the poem in the context of the “Scotti peregrini” on the continent and the spread of the cult of St. Brigid in Europe. Abstract Parmi les Irlandais ayant oeuvré sur le continent durant l’ère carolingienne, les plus célèbres sont sans doute Dungal de Saint-Denis, Pavie et Bobbio, ainsi que Donat de Fiesole. Tous les deux présentent les traits et les intérêts caractéristiques des “Scotti peregrini” de leur époque, les informations à leur sujet demeurent vagues. Dungal, d’une part, est un personnage insaisissable et encore quelques décennies plus tôt, les chercheurs maintenaient que derrière ce nom de plume se dissimulaient plusieurs figures distinctes. Donat, d’autre part, est un personnage historique relativement connu, mais sa production littéraire et les textes rattachés à sa Vita metrica sanctae Brigidae n’ont reçu que peu d’attention de la part de la communauté scientifique. Dans le présent article, je me penche sur le poème O uenerande pie, une oeuvre qui semble relier les deux Irlandais, et développe ainsi une hypothèse formulée par Mario Esposito. À la suite d’une analyse philologique et historique, je tente d’identifier l’expéditeur et le destinataire du poème. Je cherche ensuite à situer le poème dans le contexte des “Scotti peregrini” du continent et celui de la diffusion du culte de sainte Brigitte en Europe.